Sustainable lignin nanoparticles for herbicide delivery systems: preparation, characterization, and effects on target and nontarget plants - Lima, Pedro H. C.; Buri, Maria C. Shiroma; Mendonça, Rafaela S.; Favara, Gabriel M.; Biscalchim, Érica R.; Forini, Mariana M. L. H.; Cavalcante, Luiz A. F.; Grillo, Renato [UNESP] (American Chemical Society, 2025)
Recent advances in nanoscience have reduced herbicide usage while maintaining crop yields, and sustainable materials, such as lignin, have emerged as promising nanocarriers for herbicide delivery. Spherical lignin nanoparticles (SLNPs) with atrazine (SLNPs_ATZ) were designed, characterized, and applied to nontarget and target plants in this work. SLNPs_ATZ displayed spherical shapes with sizes near 178 nm by dynamic light scattering (DLS), and 136 nm by nanoparticle tracking analysis (NTA), with a 74.2% loading efficiency and a 43.26% release percentage after 168 h. Chemical computational modeling revealed lower gap energies between atrazine and lignin, indicating strong carrier/ bioactive interactions. Hydroponic experiments were conducted with butterhead lettuce with sublethal doses of atrazine (30 μg/L) for 28 days, and lettuce treated with SLNPs and SLNPs_ATZ showed no significant changes in root length/shoot area compared to the control. Lipid peroxidation and catalase (biochemical tests) showed significant differences between lettuce treated with atrazine and all other treatments. Gene expression of catalase-1 (CAT1) and GST6 genes indicated a possible stress tolerance in lettuce by SLNPs. Moreover, PER51 gene results indicated damage from SLNPs_ATZ and ATZ. Based on the weed control assessment, seeds/seedlings showed possible germination/development interference by SLNPs_ATZ. These findings highlight lignin as a sustainable molecule for developing nanocarriers with potential effects on gene expression and improved weed control.
Nanopartículas de lignina para sistemas de liberação de herbicidas sustentáveis: preparação, caracterização e efeitos em plantas-alvo e não-alvo
Keywords: Lignin; Nano-enabled agriculture; Nanoherbicides; Atrazine; Sustainable agriculture; Nontarget and target plants